Representation of the image of the minor in the publicity circulated via the Internet - Garrido Felipe; Laura Sonera-Marcos; Pilar M. García-Fernández; Ilaria Montagni; Juan Luis González-Caballero (Elsevier, 2020)
Introduction: The representation of the minor in advertisements is a topic that is scarcely studied and reflected in the bibliography, in social paediatrics as well as audio-visual communication. The aim of the present study is to describe how the minor is represented in the publicity that is conveyed through the internet, and whether or not that representation is adequate. Material and methods: An analysis was made of all the advertisements in which minors appeared during a period of two months, on three days a week, on the most visited web pages in Spain. The evaluation on how the minor was represented was carried out with an evaluation tool, constructed by the authors, based on European and Spanish legislation, which showed a high concordance between evaluators. A descriptive analysis was performed on the categorical variables, and the inter-dependent relationship was established between them using the chi-squared test. Results: A total of 173 advertisements were identified in which at least one minor appeared, which was generally represented solo (63.5%), in a natural environment (36.9%) and of school age (44.5%). The web pages of the "general press" are those that most frequently show advertisement in which minors are represented, through the use of banners (82%). In the majority of cases the inadequate use of the figure of the minor takes place using tactical representation, and not just strategic. Conclusions: The image of the minor in the publicity that is conveyed via the most visited web pages in Spain is inadequate in 2 of every 3 advertisements. This misuse of the minor is usually seen in as unjustifiably strategic, and favouring non-positive values or that they favour situations of inequality. Resumen: Introducción: La representación del menor en los anuncios de publicidad es un tema poco investigado y reflejado en la bibliografía, tanto de la pediatría social como de la comunicación audiovisual. El objetivo del presente estudio es describir cómo se representa al menor en la publicidad que se vehiculiza a través de Internet, y si esa representación es adecuada o no. Material y métodos: Se analizaron todos los anuncios en los que aparecían menores a lo largo de 2 meses, visualizando, 3 días por semana, las páginas web más visitadas en España. La valoración de cómo se representaba al menor se realizó con una herramienta de evaluación, elaborada por los autores, basada en la legislación europea y española, que mostró una alta concordancia interevaluador. Se realizó un análisis descriptivo de las variables categóricas y se estableció la relación de interdependencia entre las mismas a través de la prueba Chi-cuadrado. Resultados: Se identificaron 173 anuncios donde apareció al menos un menor, que es generalmente representado solo (63,5%), en un entorno natural (36,9%) y con edad escolar (44,5%). Las páginas web de «prensa general» son las que más frecuentemente muestran anuncios donde se representan menores, a través del uso de banners (82%). En la mayor parte de los casos el uso inadecuado de la figura del menor tiene lugar mediante la representación táctica del mismo, y no meramente estratégica. Conclusiones: El uso de la imagen del menor en la publicidad que se vehiculiza a través de las páginas web más visitadas en España es inadecuada en 2 de cada 3 anuncios. Dicho mal uso del menor suele objetivarse en la representación del mismo de forma estratégicamente no justificable, y favoreciendo valores no positivos o que favorecen situaciones de desigualdad.